PGV-0 AND PGV-1 INCREASED APOPTOSIS INDUCTION OF DOXORUBICIN ON MCF-7 BREAST CANCER CELLS - Edy Meiyanto (Pharmacon: Jurnal Farmasi Indonesia, 2011)
As chemotherapeutic backbone for breast cancer therapy, doxorubicin showed various side effects and induced resistancy of breast cancer cells. Development of targeted therapy on breast cancer focused on combinatorial therapy of doxorubicin and molecular targeted agents. PGV-0 and PGV-1, a curcumin analogue showed potency as co-chemotherapeutic agent with doxorubicin. Our previous study of PGV-0 and PGV-1 showed cytotoxic activity in T47D cells. Therefore, the aim of this research is to examine the synergistic effect of PGV-0, PGV-1 on the cytotoxic activity of doxorubicin through cell cycle modulation and apoptotic induction on MCF-7 breast cancer cell lines. The cytotoxic assay of PGV-0, PGV-1, doxorubicin, and their combination were carried out by using MTT assay. Cell cycle distribution and apoptosis were determined by flowcytometer FACS-Calibur and the flowcytometry data was analyzed using Cell Quest program. Single treatment of PGV-0, PGV-1 and doxorubicin showed cytotoxic effect on MCF-7 with cell viability IC50 value 50 µM, 6 µM and 350 nM respectively. Single treatment of Doxorubicin 175 nM induced G2/M arrest. Single treatment of PGV-0 5 µM induced G2/M arrest while in higher dose 12.5  µM, PGV-0 induced apoptosis. Combination of doxorubicin 175 nM and PGV-0 5 µM induced apoptosis. Combination of doxorubicin 175 nM and PGV-0 12.5 µM also increased apoptosis induction. Single treatment of PGV-1 0.6 µM induced G1 arrest while in higher dose 1.5  µM, PGV-1 induced apoptosis. Combination of doxorubicin 175 nM and PGV-1 0.6 µM induced apoptosis. Combination of doxorubicin 175 nM and PGV-0 1.5 µM also increased apoptosis induction. PGV-0 and PGV-1 are potential to be delevoped as co-chemotherapeutic agent for breast cancer by inducing apoptosis and cell cycle modulation, but the molecular mechanism need to be explored detail.  Key words: PGV-0, PGV-1, doxorubicin, co-chemotherapy, breast cancer, cell cycle arrest, apoptosis